Analysis of Body Odor on Students’ Learning Comfort - Jeta Amina Siahaan; Silvia Mariah Handayani (International Journal of Educational Practice and Policy, 2025)
Comfort in the learning process plays an important role in supporting optimal learning outcomes among university students. However, certain aspects of the learning environment that may influence this comfort are often overlooked, including the presence of body odor. Unpleasant body odor can disrupt students’ concentration, reduce psychological comfort, and negatively affect social interactions during academic activities. This study aims to examine the relationship between body odor and students’ learning comfort in higher education settings. A quantitative approach with a survey method was employed, using questionnaires as the primary instrument for data collection. The research involved 36 students selected through purposive sampling based on criteria relevant to the study objectives. The collected data were analyzed using correlation analysis to determine the strength and direction of the relationship between body odor and learning comfort. The results indicate a significant relationship between body odor and students’ learning comfort, particularly affecting concentration, academic focus, and the overall classroom atmosphere. These findings highlight that personal hygiene, especially body odor management, is an important factor in creating a healthy, comfortable, and supportive learning environment in higher education institutions.